Purpose-orientated stocking of procedure trolleys saves time in busy Emergency Centres - Furstenburg, Phillip Pieter (Division of Emergency Medicine, 2020)
Background and aim Inefficient storage and sourcing of routinely required consumables located on procedure trolleys results in time wasted when preparing for common procedures in Emergency Centres, contributing to poor efficiency and quality of care. We designed a novel purpose-orientated procedure trolley, and evaluated its impact on time spent on procedure preparation and efficiency. Methods In an urban emergency centre, eight participants were measured each day over 24 days, once using the contemporary setup and once using the modified procedure setup. During each simulation, efficiency markers were assessed (time spent on procedure preparation, steps taken, stops made, and amount of time participants had to open a drawer to locate required items). Results The mean time required to collect the required items for IV cannulation and blood sampling from the purpose-orientated trolley was 22.7 seconds(s) (SD = 3.66) compared to 49.2 s (SD = 15.45) using the contemporary trolley. There was a significant difference in mean collection time between the two trolleys (p < 0.0005). There was a significant difference (p-value < 0.0005) in all the other categories: steps taken, stops made, and drawer opening. Conclusion In our setting, stocking procedure trolleys in a purpose-orientated manner has the potential to improve efficiency by reducing time spent on procedure preparation.